Studi Eksperimental Karakteristik Perubahan Energi Potensial Pada Material Karbon Aktif Bambu Betung Sebagai Material Pad Alternatif - Saprisandi, Fikry; Wijaksana, Hendra; Surya, Teddy Prananda (Teknik Desain Mekanika; Vol 14 No 1 (2025): Januari 2025 : Teknik Desain Mekanika, 2025)
Abstract In an effort to increase the efficiency of electricity use for the cooling system, a direct evaporative cooling system was developed which is more energy efficient, environmentally friendly and produces significant cooling. The main component of a direct evaporative cooling system is the cooling pad material. In this research, a cooling pad material made from betung bamboo was developed, which was carbonized at various carbonization temperatures of 400?C, 500?C, 600?C, 700?C and 800?C, then activated at a temperature of 600?C and produced active carbon material from betung bamboo. The next test was carried out to obtain the characteristics of potential energy changes in the active carbon material of betung bamboo. The test results showed that the betung bamboo material which was carbonized at a temperature of 800?C and activated at a temperature of 600?C produced the highest pore potential energy, namely 8.35 x 10-8 J, with the highest capillary rise height reaching 0.748 m. As a result, it can be concluded that the smaller the pore size of the material, the higher the capillary rise and thus the greater the potential energy produced. For direct evaporative cooling system applications, it is recommended to use materials that have greater pore potential energy. Keyword: Potential energy changes, betung bamboo activated carbon material, alternative pad material